Prevalencia de metastrongylus en cerdos faenados en el matadero municipal del cantón Pasaje - Márquez Delgado, Washington Hilario (2008)
The present investigation was made in the Municipal slaughterhouse of the canton Pasaje, during a 6 months (oct 2005 to march 2006). This canton is located in the El Oro province, at the west south of Ecuador. The media annual temperature is 25,3º with a minimum of 22,3º and a maximum of 26,9º. The humidity average is of 79% with a maximum of 84% (from July to October) and a minimum of 76% (of January to April) and the fluvial precipitation averages annually is 758,5mm. The number of sampled animals was 1504 pigs, with ages between less than one year and older than one year. The diagnostic was made whit the lungs inspection to determine the parasites presence, finding out a prevalence of 12,16%. The conclusions of this investigation were the following: a) Out of 1504 sampled animals, 183 were positive, giving a prevalence of porcino Metastrongylus of 12,16%. b) According to the prevalence age of Metastrongylus in the animals less than a year was 13,20% and in the animals older than a year was 11,80%. c) According to race, the Metastrongylus prevalence in animals of high crossbred was 10,63 %, in crossbred animals was 11,42% and in Creole animals was 13,54%. d) According to the animals origin, Atahualpa was a prevalence of 11.63%, in Chilla was a prevalence of 21.95%, in El Guabo was a prevalence of 11.76%, in Huaquillas was a prevalence of 33.33%, in Pasaje was a prevalence of 11.41%, in Piñas was a prevalence of 12.82%, in Portovelo was a prevalence of 16.67%, in Santa Rosa was a prevalence of 19.48%, in Zaruma was a prevalence of 30.77% and in the province of Guayas was a prevalence of 14.29% e) According to the animals exploitation type of technical exploitation were the less affected with a prevalence of 6,82% and in the rustic exploitation animals were the most affected with a prevalence of 12,68%.